Crop rotation. VIII. Effect of crop systems on wheat yield - Santos, Henrique Pereira dos; Pereira, Luiz Ricardo; Reis, Erlei Melo (Pesquisa Agropecuaria Brasileira, 2014)
From 1980 up to 1985, at the National Wheat Research Center (CNPT), the effect of some crop systems on wheat yield was assessed. A crop rotation schedule was followed in such a way that wheat was seeded in every year or at intervals of one, two, and three winters. Treatments were arranged in randomized complete block design with four replications. Plot areas was of 120.0 m2. The seedbed for us the winter crops and corn was the traditional and soybeans direct drilled. Wheat was cropped every year and in rotations with a) rapessed, flax and white lupin; b) with rapessed, barley and white lupin; c) with subterranean clover cropped for two years and vetch. Wheat yield was higher in rotation than under cropped every year. Root disease rating showed higher values for monoculture than for the other systems of rotation. One thousand kernels weight was the yield component that presented better correlation to yield. The barley yield was higher than wheat.